Behavioral intention to receive self-financed and fully-subsidized herpes zoster vaccines among community-living older adults in Hong Kong: A random telephone survey - Xue Liang; Erdi Gu; Doug H. Cheung; Danhua Ye; Fuk-Yuen Yu; Yuan Fang; Phoenix K.H. Mo; Zixin Wang (Human Vaccines & Immunotherapeutics)
Herpes zoster (HZ) among older adults has consistently been a concern. Despite the availability of vaccines, HZ vaccination remains underutilized globally. This study investigated the behavioral intention of older adults in Hong Kong to receive self-financed or fully subsidized HZ vaccines. A random telephone survey was conducted between July and October 2023, involving 673 community-dwelling individuals aged 65 years or older. Among the 636 unvaccinated participants, 7.7% intended to receive two doses of the vaccine if self-financed, while 37.3% intended to do so if the vaccine was free. After adjusting for significant background characteristics, higher perceived susceptibility, benefits, and self-efficacy related to vaccines were associated with higher intent to vaccinate in both scenarios. Concerns regarding vaccine side effects were associated with lower intent in both scenarios. Frequent exposure to information regarding higher risk of HZ among older adults and COVID-19 survivors, as well as governmental recommendations for these groups to receive the vaccine, was associated with higher intent to vaccinate. These findings highlight the need to promote HZ vaccination among older adults with similar health systems and immunization policies, even when vaccines are available for free to older adults.